On the Inconsistency of the “Suid Gap” Hypothesis and Its Inappropriate Biochronological Use in Dating the Localities of Orce (Venta Micena, Barranco León D, and Fuente Nueva 3). Reply to Martínez-Navarro et al. Comment on “Iannucci, A. The Occurrence of Suids in the Post-Olduvai to Pre-Jaramillo Pleistocene of Europe and Implications for Late Villafranchian Biochronology and Faunal Dynamics. Quaternary 2024, 7, 11” - Alessio Iannucci (Quaternary)
According to the “suid gap” hypothesis, suids (Suidae, Mammalia) would have been absent from Europe between 1.8 and 1.2 Ma. This hypothesis has been influential owing to its putative implications for biochronology and paleoecology—Sus scrofa (the modern wild boar) would appear 1.2 Ma in a period of climatic and environmental changes, coinciding with the beginning of the Epivillafranchian and the Early–Middle Pleistocene Transition, and hominins—the arrival of Homo in western Europe would precede the “return” of pigs. However, the “suid gap” hypothesis is based on the wrong premises that suids are abundantly represented in the European fossil record before and after the “suid gap”, that this purported abundance is linked to the suid reproductive potential, and that the paleontological sites dated within the 1.8–1.2 Ma interval yielded enough remains to exclude the notion that the absence of suid is merely accidental. In a recent paper, it is shown that all these assumptions are erroneous and suid material is described from Peyrolles (France), which is dated at 1.47 ± 0.01 Ma, hence perfectly “filling the suid gap”. Some proposers of the “suid gap” hypothesis have now provided comments to this recent paper, casting doubt on the age of Peyrolles and reiterating the arbitrary statement that suids were commonly recorded and abundantly represented in the Pleistocene of Europe. There is no valid reason to question the homogeneity of the faunal assemblage of Peyrolles, which is indeed a key locality for the mammal biochronology of Europe, being the reference for MNQ 19. Suids of comparable chronology have also been found in Krimni (Greece). Moreover, the “suid gap” proposers are basically advocating the use of an interval biozone based on the temporary absence of Sus strozzii—a species not common in the Pleistocene of Europe—providing no ecological explanation for this gap, apart from speculating it would be due to competition with Homo. The defense of the “suid gap” seems motivated by its use from the “suid gap” proposers as a biochronological argument to contend that the localities of Orce in Spain (Barranco León D, Fuente Nueva 3, and Venta Micena) are older than 1.2 Ma, when they postulated suids would “reappear” in the fossil record. However, since the “suid gap” hypothesis was primarily proposed based on the absence of suids from the Orce sites (and, secondarily, from other sites biochronologically correlated with the localities of Orce, like Pirro Nord in Italy), this represents an evident example of circular reasoning.